Auxin-Induced Plasma Membrane Depolarization Is Regulated by Auxin Transport and Not by AUXIN BINDING PROTEIN1 - Paponov, Ivan A.; Dindas , Julian; Król , Elżbieta; Friz, Tatyana; Budnyk, Vadym; Teale, William; Paponov, Martina; Hedrich , Rainer; Palme, Klaus (Frontiers in Plant Science, 2019)
Auxin is a molecule which controls many aspects of plant development through both transcriptional and non-transcriptional signalling responses. AUXIN BINDING PROTEIN1 (ABP1) is a putative receptor for rapid non-transcriptional auxin-induced changes in plasma membrane depolarization and endocytosis rates. However, the mechanism of ABP1-mediated signaling is poorly understood. Here we show that membrane depolarization and endocytosis inhibition are ABP1-independent responses, and that auxin-induced plasma membrane depolarisation is instead dependent on the auxin influx carrier AUX1. AUX1 was itself not involved in the regulation of endocytosis. Auxin-dependent depolarization of the plasma membrane was also modulated by the auxin efflux carrier PIN2. These data establish a new connection between auxin transport and non-transcriptional auxin signaling.